Changes in Ukrainian digital diplomacy in the context of the 2014 crisis - Korienieva, Anna (2020)
The traditional ways of conducting diplomacy are being challenged by advances in new information and communication technology. As the environment of diplomacy is changing, diplomats are challenged and expected to incorporate new digital tools in their practice. However, the degree to which these changes have been adopted differ from country to country as it depends on various factors. As such, this thesis analyses impact of the 2014 crisis in Ukraine on its digital diplomacy. To answer this question, it compares and contrasts the employment of digital diplomacy tools by the Ukrainian ministry of foreign affairs (MFA) in two periods of time – from 1991 as the year of independence until 2014 and from 2014 till 2019. This thesis examines foundational variables such as the technological development in Ukraine as well as the institutional and legal framework that supported digital diplomacy. Furthermore, it also looks at the degree and quality of social media usage by the Ukrainian MFA and its diplomatic missions through the official institutional accounts. The results suggest that there is no direct implication or correlation between the crisis of 2014 and the state of Ukrainian digital diplomacy. This thesis nonetheless offers a valuable insight into the digital diplomacy practices of the Ukrainian MFA.